N, N-Dimethyltryptamine attenuates spreading depolarization and restrains neurodegeneration by sigma-1 receptor activation in the ischemic rat brain. (1st July 2021) - Szabó, Írisz; Varga, Viktória É.; Dvorácskó, Szabolcs; Farkas, Attila E.; Körmöczi, Tímea; Berkecz, Róbert; Kecskés, Szilvia; Menyhárt, Ákos; Frank, Rita; Hantosi, Dóra; Cozzi, Nicholas V.; Frecska, Ede; et al.
Abstract: Dimethyltryptamine (DMT), an endogenous ligand of sigma-1 receptors (Sig-1Rs), acts against systemic hypoxia, but whether DMT may prevent cerebral ischemic injury is unexplored. Here global forebrain ischemia was created in anesthetized rats and aggravated with the induction of spreading depolarizations (SDs) and subsequent short hypoxia before reperfusion. Drugs (DMT, the selective Sig-1R agonist PRE-084, the Sig-1R antagonist NE-100, or the serotonin receptor antagonist asenapine) were administered intravenously alone or in combination while physiological variables and local field potential from the cerebral cortex was recorded. Neuroprotection and the cellular localization of Sig-1R were evaluated with immunocytochemistry. Plasma and brain DMT content was measured by 2D-LC-HRMS/MS. The affinity of drugs for cerebral Sig-1R was evaluated with a radioligand binding assay. Both DMT and PRE-084 mitigated SDs, counteracted with NE-100. Further, DMT attenuated SD when co-administered with asenapine, compared to asenapine alone. DMT reduced the number of apoptotic and ferroptotic cells and supported astrocyte survival. The binding affinity of DMT to Sig-1R matched previously reported values. Sig-1Rs were associated with the perinuclear cytoplasm of neurons, astrocytes and microglia, and with glial processes. According to these data, DMT may be considered as adjuvant pharmacological therapy in the management of acute cerebral ischemia. Highlights: DMT suppressed spreading depolarization via sigma-1 receptor activation. DMT was ineffective to augment cerebral blood flow responses under ischemia. DMT restrained ischemia-related programmed neuronal death and rescued astrocytes. DMT may be considered as adjuvant therapy in acute cerebral ischemia management.